Assessing the influence of supply chain collaboration on the performance of manufacturing SMEs in Rwanda - Alexis Uwamahoro; Simon Peter Nadeem; Noor Shale Ismail; Elizabeth Wachiuri (International Journal of Industrial Engineering and Operations Management)
Purpose – This research examines how supply chain collaboration, underpinned by stakeholder trust, information sharing and strategic partnerships, impacts the performance of manufacturing SMEs in Rwanda. The focus on manufacturing SMEs is due to their vital role in the economy and their distinctive resource dynamics. Findings – The study demonstrates that supply chain collaboration, particularly through strategic partnerships and stakeholder trust, positively impacts supply chain performance. While information sharing’s influence is currently limited by technological constraints, the findings highlight the need for a comprehensive approach to address existing challenges and emphasise the crucial roles of stakeholders and policymakers in supporting SMEs’ performance. Research limitations/implications – This research contributes to a broader understanding of supply chain collaboration, its impact on performance, its interactions with other organisational factors and its implications for managerial decision-making, academic research and supply chain partnerships. Originality/value – This research is one of the few to demonstrate the impact of supply chain collaboration on the performance of manufacturing SMEs in developing countries, particularly Rwanda.